Electron Scattering from Some Fp- Shell Nuclei with Inclusion the Effect of Short-Range Correlation - Hamoudi, Adel K.; Abbas, Mahmoud A. (Iraqi Journal of Science, 2020)
The effects of short-range correlation on elastic Coulomb (charge) form factors, charge density distributions as well as root mean square charge radii of various nuclei (for instance, 46, 48, 50Ti, 52, 54Cr, 56, 58Fe, and 72, 74, 76Ge nuclei) are examined. The one- and two body terms of the cluster expansion together with the single-particle harmonic oscillator wave functions are utilized. For the purpose of embedding these effects into the formulae of charge density and form factor we employ the correlation function of Jastrow-type. These formulae depend upon the short-range correlation parameter (which instigates from the Jastrow function) and the oscillator size parameter Both and are found by the fitting to the measured elastic form factors. It is noticed that the embedding of short-range correlation effects into the calculations of and is a requisite for the achievement of a vital change in the computed results and remarkably vital for the characterization of the measured data.